2008
DOI: 10.2147/ceg.s3887
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of viral hepatitis in Sudan

Abstract: Hepatitis virus infections are the most common cause of liver disease worldwide. Sudan is classified among the countries with high hepatitis B virus seroprevalence. Exposure to the virus varied from 47%–78%, with a hepatitis B surface antigen prevalence ranging from 6.8% in central Sudan to 26% in southern Sudan. Studies pointed to infection in early childhood in southern Sudan while there was a trend of increasing infection rate with increasing age in northern Sudan. Hepatitis B virus was the commonest cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 40 publications
(53 reference statements)
1
43
4
Order By: Relevance
“…Three hundred and thirty five participants were surveyed in this study. Past or ongoing infection among the study group, measured by AntiHBcore (IgG), was 34% which was less than that found in other study among Sudanese population [4]. This may be explained by the health education offered to village midwives during their training program.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Three hundred and thirty five participants were surveyed in this study. Past or ongoing infection among the study group, measured by AntiHBcore (IgG), was 34% which was less than that found in other study among Sudanese population [4]. This may be explained by the health education offered to village midwives during their training program.…”
Section: Discussioncontrasting
confidence: 63%
“…While carrier rate (positive HBsAg) 6.8% to 26%. So, Sudan considered as one of the countries with a high endemicity [4]. HBV infection is an important occupational hazard for village midwives.…”
Section: Background Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sudan, the prevalence of HCV among pregnant women (0.6%) is lower than that in the general population (2.2% to 3%) [30,51,52]. Therefore, the northern part of the River Nile region is considered to be a highly endemic area for HCV and the southern part is less endemic, with a very low prevalence among pregnant women.…”
Section: Hcv Among Pregnant Women In the Arabian Nile River Regionmentioning
confidence: 99%
“…This result is supported with a previous study done on the prevalence of HBV in Sudan and in line with another study investigating the causes of chronic liver disease in Pakistan. 17,18 Undetermined causes of liver disease in this study are mainly due to death of patients before complete work up has taken place. Nevertheless, other rare conductions like: non-alcoholic steato hepatitis, hemochromatosis, storage liver disease, alfa-1 antitrypsin deficiency, both primary and secondary biliary cirrhosis and cryptogenic liver cirrhosis should all be considered.…”
Section: Discussionmentioning
confidence: 99%